Controlling of dielectrical and optical properties of hydroxyapatite based bioceramics by Cd content - Kaygili, Omer; Keser, Serhat; Ates, Tankut; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
Cadmium included hydroxyapatite (HAp) based bioceramics were synthesized by sol-gel method. The effects of Cd ions on their crystallinity, phase structure, dielectric and optical properties were investigated using X-ray diffraction (XRD), Fourier transform infrared (FTIR) and dielectric impedance spectroscopy methods, respectively. The crystallinity of the samples indicates an obvious change with the increasing content of the Cd dopant. The amount of Cd dopant affects the phase composition of the HAp. All the samples are consisted of nanoparticles (ranging from 34 to 86 nm). The relative permittivity of the HAp is changed with Cd content. The alternating current conductivity results suggest that all the bioceramics exhibit an insulator behavior. It is evaluated that the dielectric and optical properties of HAp can be controlled by Cd content (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Sol-gel method; Hydroxyapatite; Dielectric; Cadmium